Entrustment decisions and the clinical team: A case study of early clinical students. Issue 3 (29th December 2020) - Pinilla, Severin; Kyrou, Alexandra; Maissen, Norina; Klöppel, Stefan; Strik, Werner; Nissen, Christoph; Huwendiek, Sören
Abstract: Purpose: Clinical learning contexts influence how medical students engage with entrustment decisions. However, it is unclear how students and health care team members perceive the entrustment decision process. This study explored which factors students and team members consider relevant to entrustment decisions in early clinical rotations. Methods: The authors conducted a case study at an academic teaching hospital, interviewing 28 medical students and four health care team members during the clerkship year. Within a social constructivist epistemology, we explored students' and health care team members' perceptions of ad hoc entrustment decisions using semi‐structured interviews. Transcripts from the interviews and notes from feedback rounds with students were used for analysis. Results: Medical students in their core clerkship year perceived clinical residents as critical educational gatekeepers and key facilitators of entrustment decisions. Another important theme emerged around students' motivation, initiative and willingness to engage with the health care team and patients. Students actively engaged in trust formation processes with different health care team members. The entrustment decision process was perceived as multilateral and dynamic, involving all health care team members and patients. Multiple entrusting supervisors for clerkship students, including nurses and psychologists, emerged from our interview data. They assumed an active role in negotiating entrustment decisions both with and for clerkship students, either facilitating or hindering opportunities. The entrustment decisions emerged as a result of a multifaceted supervisor network interaction. Conclusions: Supervising residents' ability to integrate students into clinical teams seems to be a critical factor in facilitating entrustment opportunities for clinical activities. Students' active management of informal supervisor networks of health care team members and these team members' willingness to assume responsibility for the students' education emerged as relevant aspects for ad hoc entrustment. Our data suggest that supervision from different health professionals is beneficial for clinical education of medical students and merits further exploration. Abstract : Entrustment, often considered something supervisors give to trainees, was found to sometimes be taken by virtue of students' active management of their informal supervisory networks.